A historical biogeography of megadiverse Sericini—another story "out of Africa"?. (19th April 2016) - Eberle, Jonas; Fabrizi, Silvia; Lago, Paul; Ahrens, Dirk
Abstract: Megadiverse insect groups present special difficulties for biogeographers because poor classification, incomplete knowledge of taxonomy, and many undescribed species can introduce a priori sampling bias to any analysis. The historical biogeography of Sericini, a tribe of melolonthine scarabs comprising about 4000 species, was investigated using the most comprehensive and time‐calibrated molecular phylogeny available today. Problems arising through nomenclatural confusion were overcome by extensive sampling (665 species) from all major lineages of the tribe. A West Gondwanan origin of Sericini ( c . 112 Ma) was reconstructed using maximum parsimony, maximum‐likelihood and model‐based ancestral area estimation. Vicariance in the tribe's earliest history separated Neotropical and Old World Sericini, whereas subsequent lower Cretaceous biogeography of the tribe was characterized by repeated migrations out of Africa, resulting in the colonization of Eurasia and Madagascar. North America was colonized from Asia during the Cenozoic and a lineage of "Modern Sericini" reinvaded Africa. Diversification dynamics revealed three independent shifts to increased speciation rates: in African ant‐adapted Trochalus, Oriental Tetraserica, and Asian and African Sericina. Southern Africa is proposed as both cradle and refuge of Sericini. This area has retained many old lineages that portray the evolution of the African Sericini fauna as a series of taxon pulses.